2016
DOI: 10.1007/s11605-016-3167-2
|View full text |Cite
|
Sign up to set email alerts
|

Should We Use the Model for End-Stage Liver Disease (MELD) to Predict Mortality After Colorectal Surgery?

Abstract: We sought to determine the accuracy of the Model for End-Stage Liver Disease and the Mayo Clinic Postoperative Mortality Risk in Patients with Cirrhosis Calculator in patients with ascites who underwent colorectal surgery. The National Surgical Quality Improvement Program database was queried for patients with ascites who underwent a major colorectal operation. Predicted 90-day mortality rate based on the Model for End-Stage Liver Disease and 30-day mortality based on the Mayo Clinic Postoperative Mortality Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…While cirrhosis is not a direct variable in NSQIP, the variable of ascites is specific to liver disease, and specifically excludes malignant ascites. The presence of ascites as a marker for cirrhosis is previously reported [36, 38], and within NSQIP has generally been accepted as a sound substitute for cirrhosis, helping to identify patients with chronic liver disease for the study of surgical outcomes [9, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cirrhosis is not a direct variable in NSQIP, the variable of ascites is specific to liver disease, and specifically excludes malignant ascites. The presence of ascites as a marker for cirrhosis is previously reported [36, 38], and within NSQIP has generally been accepted as a sound substitute for cirrhosis, helping to identify patients with chronic liver disease for the study of surgical outcomes [9, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies, we investigated the effect of ascites on risk prediction for patients with chronic liver disease and compared patients of similar MELD stratum differentiated only by the presence of ascites. Other studies have also shown associations of increased postoperative risk with the presence of ascites [9, 24, 36] and that MELD underestimated risk for postoperative mortality for significant portion of patients (~ 25%) undergoing liver transplantation [23]. While it is not entirely clear the etiology of increased complications and death in patients with ascites, some theories exist.…”
Section: Discussionmentioning
confidence: 99%
“…There was no uniform method for confirming diagnosis of liver cirrhosis. Five studies were based on coding of nationwide databases [12,13,[16][17][18]. The coding criteria differed between them.…”
Section: Diagnosis Of Liver Cirrhosismentioning
confidence: 99%
“…There was heterogenous reporting of mortality rates which was available in only ten studies [5,10,11,13,16,[18][19][20][21][22] (Table 4). Rates ranged from 0 to 37%.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation